Analisis Penerapan Sistem Layanan Administrasi Kependudukan Online (SILAMO) - Kurniawansyah; Haryadi, Wahyu; Ismawati; Syafruddin; Rahayu, Sri (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The Online Population Administration Service System is a system whose service process is carried out in the local village which includes Population Biodata Recording Services, Family Card Issuance Services, Moving In and Out Information Issuance Services, Birth Certificate Issuance Services, Death Certificate Issuance Services, Marriage Certificate Issuance Services, Divorce Certificate Issuance Services, Child Recognition and Validation Certificate Issuance Services, Citizenship Change Certificate Issuance Services, Marriage Cancellation Certificate Issuance Services, Residence Certificate Issuance Services. Many people in the villages do not yet know about the online services provided by the Population and Civil Registration Service of Sumbawa Regency, so many people still come to the office to take care of population documents. This is due to the lack of socialization carried out by the Village regarding the Online Services of the Population and Civil Registration Service of Sumbawa Regency. The purpose of this study was to analyze the Implementation of the Online Population Administration Service System. The quantitative associative research method was used in this study, the technical data analysis in this study used the Method of Successive (MSI). The results of the study show that the implementation of SILAMO makes it easier for the public to access population administration services anytime and anywhere, without having to come to a government office. This makes it very easy, saves time, and reduces transportation costs. The government can more easily provide information quickly and efficiently, and speed up the service process to the public.